Health and Performance Implications of Future Work under Disrupted Schedules, Working Environments and Careers - Wilson, Micah (2019)
Fatigue is a physiological state of reduced mental or physical performance capability that causes direct negative impacts on performance. Fatigue results from a number of factors, such as: transient or chronic sleep deprivation, working conditions (e.g., high workload), and circadian processes. A great deal of research has established that excessive fatigue in shift-workers in complex work environments (e.g., medical staff, military domains) can lead to increased human error, decreased productivity and also negative long-term impacts on health and wellbeing. However, changes in working practices (e.g., technological advancements; 24/7 global-connection) has meant that employees across a range of sectors no longer are constrained to the standard working week, and also are at risk of fatigue-related impairments.